Über den Einfluss der Fußgeometrie auf die Energieeffizienz beim zweibeinigen Gehen - Römer, Ulrich Johannes (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2019)
The influence of foot geometry on energy efficiency in bipedal walking is investigated. A method for the optimization of the foot geometry of a bipedal robot is developed. It is based on a planar model with arbitrary convex foot geometry in combination with a hybrid zero dynamics based controller. Optimal gaits and foot geometries are determined. The average energy consumption can be reduced by more than 80% compared to a model with point feet.